The Effectiveness of Quizalize-Based Learning in Enhancing First-Semester Students’ Reading Comprehension - Putri Anwar Dani; Virgiyanti, Diska; Arina Fatya Mansikana; Ulfa Yuliasari (INNOVATION RESEARCH JOURNAL, 2026)
This study explores the effectiveness of Quizalize, an interactive quiz game application, in enhancing reading comprehension among first-semester English Language Teaching (ELT) students. Reading is a foundational skill in English language learning, yet students in the Basic Reading course have demonstrated suboptimal comprehension levels. Quizalize, designed for classroom training and assessment, offers accessible and engaging quizzes, making it a promising tool for improving student outcomes. The study employed a quantitative, quasi-experimental design with an active control group. Sixty first-semester ELT students at Darussalam Gontor University were randomly selected through probability sampling. Data were collected through tests and documented evidence, then analyzed using SPSS 22. Results indicate that Quizalize significantly enhances reading comprehension, with a Sig.(2-tailed) value of 0.000 < 0.05, confirming its effectiveness. Based on these findings, Quizalize is recommended for Basic Reading courses, as it promotes critical thinking and comprehension. Teachers are encouraged to integrate Quizalize to help students better understand key information within texts.